Utilisation of chicken eggshell nanopowder on physicochemical quality, microstructure, and amino acid profile of beef patties - Herly Evanuarini; Agus Susilo; Uun Yanuhar; Adelya Desi Kurniawati (Czech Journal of Food Sciences, 2023)
Chicken eggshells are a source of calcium and protein that can be added to restructured meat products, including patties. This study aimed to improve the chemical quality of beef patties with the addition of chicken eggshell nanopowder, including pH, protein content, ash content, fat content, antioxidant activity, calcium, microstructural quality, and identification of amino acid profiles. The method used in this study was a laboratory experiment arranged in a completely randomised design with five treatments: without the addition of chicken eggshell nanopowder as a control, the addition of chicken eggshell nanopowder 0.1, 0.3, 0.5, and 0.7% (w/w) with five replications. Data were analysed using the analysis of variance. It was followed by Duncan's multi-range test when the differences were significant or very significant. The research results show that the addition of chicken eggshell nanopowder to beef patties had a very significant effect (P < 0.01%) on pH, protein content, ash content, fat content, antioxidant activity, calcium, microstructural quality through scanning electron microscopy, and several amino acids. The addition of 0.7% chicken eggshell nanopowder could improve the chemical quality of the beef patties. The patty matrix was uniform and compact, and the air voids were getting tighter with the addition of chicken eggshell nanopowder, which was increasing based on scanning electron microscopy observations. Moreover, beef patties had various types of amino acids to achieve the best treatment.